Phytoaccumulation of zinc and iron by Jatropha curcas grown in used lubrication oil-contaminated soil - O.P, Abioye; P., Agamuthu; A., Abdul Aziz (Malaysian Journal of Science, 2010)
Contamination of soil by heavy metals from used lubricating oil constitutes major environmental problems due to its negative impacts on humans and environment. Plants that possessed bioaccumulation potential offered green remediation approach for the removal of such heavy metal contaminants. In this study, heavy metal accumulation potential of Jatropha curcas was studied in soil contaminated with 2.5% and 1% (w/w) used lubricating oil and enhanced with organic wastes [banana skin (BS), brewery spent grain (BSG) and spent mushroom compost (SMC)] for 180 days under room condition. At the end of 180 days, accumulation of Fe and Zn were recorded in J. curcas tissues (roots, stems and leaves) in all the treatments. 9.94 mg/kg to 26.34 mg/kg of Fe and 4.14 mg/kg to 8.45 mg/kg of Zn were recorded in the roots of J. curcas in soil contaminated with 2.5% oil. Organic wastes amendments enhanced the bioaccumulation of Fe and Zn with about 25% compared with control treatments without organic wastes amendment. The result of this study suggests that J. curcas has a good potential for bioaccumulation of Fe and Zn in contaminated soil.